2020
DOI: 10.1101/2020.12.08.417014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative 3D Imaging of the Cranial Microvascular Environment at Single-Cell Resolution

Abstract: Vascularization is critical for skull development, maintenance, and healing. Yet, there remains a significant knowledge gap in the relationship of blood vessels to cranial skeletal progenitors during these processes. Here, we introduce a quantitative 3D imaging platform to enable visualization and analysis of high-resolution datasets (>100 GB) throughout the entire murine calvarium. Using this technique, we provide single-cell resolution 3D maps of vessel phenotypes and skeletal progenitors in the frontopar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…These bone marrow niches maintain populations of immune cells in the meninges during homeostasis and allow for rapid recruitment in response to injury or autoimmunity. [29][30][31][32] Microscopy enables visualization of immune traffic through specialized ossified vascular channels. 29 These specialized bone marrow niches can imprint developing cells with distinct properties and play a role in tolerance to CNS antigens.…”
Section: Skullmentioning
confidence: 99%
See 1 more Smart Citation
“…These bone marrow niches maintain populations of immune cells in the meninges during homeostasis and allow for rapid recruitment in response to injury or autoimmunity. [29][30][31][32] Microscopy enables visualization of immune traffic through specialized ossified vascular channels. 29 These specialized bone marrow niches can imprint developing cells with distinct properties and play a role in tolerance to CNS antigens.…”
Section: Skullmentioning
confidence: 99%
“…However, recent studies have shown that the skull and vertebral bodies are not simply structural barriers that protect against mechanical injuries; they contain specialized pockets of bone marrow that are connected to dural sinuses and meningeal veins (Figure 1). These bone marrow niches maintain populations of immune cells in the meninges during homeostasis and allow for rapid recruitment in response to injury or autoimmunity 29‐32 . Microscopy enables visualization of immune traffic through specialized ossified vascular channels 29 .…”
Section: The Immunology Of Cns Barriers and Anatomymentioning
confidence: 99%
“…When using intact skull methods in older animals, the gradual thickening of the skull can also result in lower quality imaging 20,21 . As a final note, there has been increased attention paid to skull microvasculature environment 22 and the interaction with the meninges. Our results demonstrating increased skull thickness with age indicate possible age-related effects on these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues fixed with Bouin's solution have remnant yellow coloration that enhances the autofluorescence signal. However, Rindone et al have demonstrated adequate bone tissue clearing transparency without decalcification (8).…”
Section: Discussionmentioning
confidence: 99%